Room temperature ionic liquid carbon nanotube paste electrodes: Overcoming large capacitive currents using rotating disk electrodes - Kachoosangi, RT; Wildgoose, G; Compton, R (2007)
The voltammetric response of graphite or carbon nanotube paste electrodes, which incorporate the room temperature ionic liquid, N-butyl-N-methyl pyrrolidinium bis(trifluoromethylsulfonyl) imide or [C4mpyrr] [NTf2], (RTIL-CNTPE and RTIL-CPE respectively) as the binder, towards anionic, cationic and neutral redox probes is examined and compared to conventional paste electrodes which use mineral oil as the binder. The RTIL paste electrodes are found to suffer from very large background currents due to capacitive charging. This is exacerbated further when CNTs are combined with RTILs in the paste. The large charging currents obscure any Faradaic processes of interest, especially at low analyte concentrations. By employing steady state voltammetry at a rotating disk electrode made of the RTIL pastes this problem can be overcome. This allows the electroanalytical properties of these interesting electrode substrates, which combine the attractive properties of CNTs with RTILs to be further explored and developed. © 2007 Wiley-VCH Verlag GmbH and Co. KGaA.